Picturesque Trinidad - Rice, Ben (My University, 2009)
Image depicts several trees in what appears to be a landscaped area on the island of Trinidad.
Colour: Black and White; Style: Portrait; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Shade trees--Trinidad and Tobago; [1911]